A new permanent, low-cost, low-power SO2 camera for continuous measurement of volcanic emissions - Wilkes, Thomas Charles; Pering, Tom David; Aguilera, Felipe; Layana, Susana; Nadeau, Patricia; Kern, Christoph; McGonigle, Andrew John Samuel; Aguilera, Mauricio; Zhu, Chengxi (Frontiers in Earth Science, 2023)
Since its introduction to volcanology in the mid-2000s, the SO2 camera has become an important instrument for the acquisition of accurate and high time-resolution SO2 emission rates, aiding in hazard assessment and volcanological research. However, with the exception of a few locations (Stromboli, Etna, Kīlauea), hitherto the majority of measurements have been made on discrete field campaigns which provide only brief snapshots into a volcano’s activity. Here, we present the development of a new, low-cost, low-power SO2 camera for permanent deployment on volcanoes, facilitating long-term, quasi-continuous (daylight hours only) measurements. We then discuss preliminary datasets from Lascar and Kīlauea volcanoes, where instruments are now in continuous operation. Further proliferation of such instrumentation has the potential to greatly improve our understanding of the transient nature of volcanic activity, as well as aiding volcano monitoring/eruption forecasting.